Orientalism and Children’s Literature: An Analysis of Adult-Children Relations in a Picture Book Entitled “Bad Bad Bunny Trouble” Written by Hans Wilhelma - Dosy Janwar Gulfusarak (Universitas Pendidikan Indonesia (UPI), 2014)
The present study examines adult-children relations in a picture book entitled “Bad Bad Bunny Trouble” by Hans Wilhelm from an Orientalist perspective. The focuses of the study are the portrayal of children in the picture book and the meanings made from the portrayal. Two main theoretical frameworks were used in this study. The first theoretical framework is Orientalism from Said (2003). The second theoretical framework is visual analysis theory from Nodelman (1988) which was used to analyze the pictures. Children are portrayed as the Other while Adults are the Self. The findings indicate that as the Other, children are marginalized and adults take center stage. As the center, adults take charge and expect children to fulfill the adults’ expectation to prepare the children for adulthood. From Orientalism perspective, the adults-children relation in the picture book is the representation of the binary opposition of Self and Other in Orientalism.Keywords: Orientalism, Self, Other, visual analysis, picture book